Development Planning of Oongan Dam Tourism Area as Community-Based Tourism in Denpasar City - Anak Agung Gede Willy Kencana Putra; Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
This study explores the potential of Dam Oongan to be developed as a tourist attraction, highlighting its beautiful garden, jogging tracks, swimming pools, and culinary tours. The research addresses two main questions: the existing attractions around Oongan Dam and the development plan for community-based tourism in Denpasar, Bali. Using a qualitative approach, data were collected through in-depth interviews, field observations, and document analysis. The findings reveal significant attractions such as good accessibility, adequate amenities, and various attractions including Dam Oongan and its gardens. However, the development plan is hindered by the absence of a dedicated management institution and unclear community values. Recommendations include forming a management institution and clarifying community vision.